Peran Transendensi dalam Pendidikan Profetik Terhadap Kehidupan Kontemporer - Wahyu Ningsih,; Lasmanah Lasmanah,; Fitria Khoirunnisa , (Jurnal Bintang Pendidikan Indonesia, 2024)
Prophetic education is a process of transferring knowledge and values ​​which aims to get closer to God and nature while understanding them to build an ideal social community (khaira ummah). The pillar of transcendence is an important milestone for building oneself to strengthen one's faith (tu'minu billah) in Allah SWT. The goal of transcendence is to cleanse oneself from the flow of hedonism and restore human nature to return to God. This research method uses a qualitative method, namely in the form of data described through words, not through numbers. Meanwhile, the technical data analysis used is the literature study method or literature study. Recognition of the existence of a transcendental structure interprets the reality of the existence of pure ideas, the source of which is outside the human self, has far and wide implications for life.